2009
DOI: 10.3382/ps.2008-00252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1α-hydroxycholecalciferol on growth performance, parameters of tibia and plasma, meat quality, and type IIb sodium phosphate cotransporter gene expression of one- to twenty-one-day-old broilers

Abstract: This experiment was conducted to investigate the effects of 1alpha-hydroxycholecalciferol (1alpha-OH D3) on the growth performance, tibia and plasma parameters, nutrient utilization, meat quality of the breast and thigh, and type IIb sodium phosphate cotranspoter gene expression of broilers. A total of 96 males of 1-d-old Arbor Acres broilers were randomly assigned to 8 cages of 12 birds each. Two dietary treatments were applied to 4 cages each. Diet 1 was prepared as the basal diet (nonphytate phosphorus, 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 34 publications
11
41
0
6
Order By: Relevance
“…Similarly, our results also confirm the previous reports that no significant effects were observed on growth performance of broiler chickens at 21 days of age after supplementation of the diet with 1α(OH)D 3 , 25(OH)D 3 , or 1,25(OH) 2 D 3 . Furthermore, 1α(OH)D 3 did not alter bone breaking strength, tibia calcium, and phosphorus content in broiler chickens at 21 days of age (Han et al, 2009). Consistently, we also found that vitamin D 3 metabolites did not improve bone breaking strength and bone mineral deposition after feeding for three weeks.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Similarly, our results also confirm the previous reports that no significant effects were observed on growth performance of broiler chickens at 21 days of age after supplementation of the diet with 1α(OH)D 3 , 25(OH)D 3 , or 1,25(OH) 2 D 3 . Furthermore, 1α(OH)D 3 did not alter bone breaking strength, tibia calcium, and phosphorus content in broiler chickens at 21 days of age (Han et al, 2009). Consistently, we also found that vitamin D 3 metabolites did not improve bone breaking strength and bone mineral deposition after feeding for three weeks.…”
Section: Discussionsupporting
confidence: 73%
“…Dietary supplementation of 1,25(OH) 2 D 3 significantly regulates the expression of NaPi-IIb cotransporter in the intestine of rats (Katai et al, 1999). In broilers, 1α(OH)D 3 also has a similar effect on regulation of intestinal NaPi-IIb cotransporter gene expression (Han et al, 2009). Here, we also demonstrated that vitamin D 3 metabolites could rapidly induce the levels of NaPi-IIb cotransporter mRNA in the intestine of broiler chickens.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Since, the efficiency of conversion for cholecalciferol to active metabolites and 1α, 25-(OH) 2 -D 3 ] in the biological systems is not 100%, serum 25-OH-D 3 is considered the best available biomarker of exposure to dietary sources of VIT-D3. Theses observation have stimulated the research towards the study of using VIT-D3 metabolites in poultry feed in other to improve bird productivity, bone calcification and egg sell quality (Garcia et al, 2001;Keshavarz, 2003;Driver et al, 2006;Shim et al, 2008;Chou et al, 2009;Han et al, 2009;Valkonen at al., 2010). Nowadays, animal welfare is a big concern in the livestock industry of developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary vitamin D 3 (Rao et al, 2006), 1,25-(OH) 2 D 3 (Edwards, 2002), and 1α-OH D 3 Han et al, 2009) increased the serum Ca and Pi concentrations in broilers. In contrast, Driver et al (2008) reported that 1α-OH D 3 did not affect the serum Pi content in non-obese diabetic mice.…”
Section: Discussionmentioning
confidence: 99%